Deutschland und Europa. Wächst zusammen, was zusammengehört? - Akademie der Wissenschaften in Hamburg (Abhandlungen der Akademie der Wissenschaften in Hamburg, 2013)
Is Europe in crisis? Is there such a thing as European identify beyond economic and political integration? What common features can be found in history and in the present that foster unity? And what is Germany's role in this process? These were among the questions raised in a lecture series held at the Academy of Sciences in Hamburg from November 2011 to February 2012. The volume present responses by Heimo Reinitzer, Gabriele Clemens, Michael Borgolte, Dan Diner, Friedrich Wilhelm Graf, and Anja Pistor-Hatam.; Heimo Reinitzer, Akademie der Wissenschaften in Hamburg.